STUDY ON THE TOXICITY OF SUMICIDIN ,FENVALERATE ,AND ITS RESIDUES IN LARVAE OF COMMON CARP FISH Cyprinus carpio - Kaddou, Ibrahhim; AL – Mashhadani, Hussain (Iraqi Journal of Science, 2024)
Results of laboratory investigation in larvae of common carp fish , Cyprinus carpio exposed to Sumicidin ,Fenvalerate, and its residue, normally used as air sprays to control insects, that this insecticide was toxic to fish larvae. After exposure to the insecticide, some larvae were immediately killed ; others showed abnormal behavior and eventually either died or recovered depending on sumicidin dose received.The LC50 of Sumicidin to fish larvae exposed to insecticide during a period of 96 hour was 0.024 mg/L for fish 4-6 gm